2017
DOI: 10.1111/exd.13123
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide analysis of copy number variants in alopecia areata in a Central European cohort reveals association with MCHR2

Abstract: Alopecia areata (AA) is a common hair loss disorder of autoimmune aetiology, which often results in pronounced psychological distress. Understanding of the pathophysiology of AA is increasing, due in part to recent genetic findings implicating common variants at several genetic loci. To date, no study has investigated the contribution of copy number variants (CNVs) to AA, a prominent class of genomic variants involved in other autoimmune disorders. Here, we report a genomewide- and a candidate gene-focused CNV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…The emergence of these signatures further refined the focus using small-molecule JAK inhibitors. Recently, associations between alopecia areata and copy number variations (CNV) were found using genome-wide scans (Box 3) 59 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…The emergence of these signatures further refined the focus using small-molecule JAK inhibitors. Recently, associations between alopecia areata and copy number variations (CNV) were found using genome-wide scans (Box 3) 59 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…While CNVs are present in every human genome, burden analyses in cohorts of congenital disorders have shown that affected patients are more likely to harbour large gene‐disrupting (genic) CNVs than unaffected individuals . Likewise, common CNVs have been identified in association studies of autoimmune diseases such as Crohn's disease, systemic lupus erythematosus (SLE), psoriasis, rheumatoid arthritis (RA), type 1 diabetes, and AA …”
Section: Introductionmentioning
confidence: 99%
“…Das Team Johannes Fischer/PD Dr. med. Franziska Degenhardt vom Institut für Humangenetik in Bonn hat zum ersten Mal mit molekulargenetischen Methoden eine bestimmte, mit dem Melanin‐Stoffwechsel in Zusammenhang stehende Region im menschlichen Genom als Risikofaktor für die Erkrankung identifizieren können . Frau Dr. rer.…”
unclassified